Beyond TOEFL: multivariate predictors of academic achievement in Chinese international students - Yan, Yuyang; Meyer, Blanca (Frontiers in Education, 2025)
This study aims at examining if TOEFL score, demographic characteristics and environmental factors predict the academic success (through GPA) of selected Chinese international students. Using the cognitive predictor model of Molnár and Kocsis as theoretical framework and Astin’s Input-Environment-Outcomes (I-E-O) model as conceptual paradigm, the roles of other input variables (demographic characteristics) and environmental factors (self-confidence, study habits, social skills, previous learning experiences) may as well impact the Chinese international students’ GPA, independently from TOEFL. A total of 201 survey participants were recruited through snowball sampling. Results revealed that majority of the participants gained a TOEFL score of 90 and above with majority earning a GPA of 3.0 and above. This indicated a good academic performance among the participants. Pearson correlation analysis found a moderate positive correlation between TOEFL score and GPA (r = 0.30, p < 0.001) while each of the subsections of TOEFL demonstrated statistically significant positive correlations with GPA: reading (r = 0.287, p < 0.001), listening (r = 0.217, p = 0.002), speaking (r = 0.155, p = 0.028), and writing (r = 0.361, p < 0.001). Years living in the US, Major and Institution were found to predict the participants’ GPA while two indicators of self-confidence (confidence in finishing the program and confidence in earning 3.0 GPA) also predicted their GPA. Likewise, one indicator of study habits (habits are adequate to maintain good grades) is also a predictor of GPA. A Hierarchical Linear Modeling (HLM) analysis revealed that Input variables (Years Living in the US, Institution, Major) explained 7.7% of the variance in students’ GPA. Environmental variables (Self-Confidence, Study Habit) explained an additional 11.5% when controlling Input factors. Thus, a total of 19% of the variation in GPA was explained by Input and Environment factors alone. HLM analysis revealed that the TOEFL score was the strongest factor predicting GPA but only explains 6.9% of the total variation.